Impacts of Neonicotinoids on the Bumble Bees Bombus terrestris and Bombus impatiens Examined through the Lens of an Adverse Outcome Pathway Framework. (21st January 2021) - Camp, Allison A.; Lehmann, David M.
Abstract: Bumble bees ( Bombus sp.) are important pollinators for agricultural systems and natural landscapes and have faced population declines globally in recent decades. Neonicotinoid pesticides have been implicated as one of the reasons for the population reductions in bumble bees and other pollinators due to their widespread use, specificity to the invertebrate nervous system, and toxicity to bees. Adverse outcome pathways (AOPs) are used to describe the mechanism of action of a toxicant through sequential levels of biological organization to understand the key events that occur for a given adverse outcome. We used the AOP framework to organize and present the current literature available on the impacts of neonicotinoids on bumble bees. The present review focuses on Bombus terrestris and B. impatiens, the 2 most commonly studied bumble bees due to their commercial availability. Our review does not seek to describe an AOP for the molecular initiating event shared by neonicotinoids, but rather aims to summarize the current literature and determine data gaps for the Bombus research community to address. Overall, we highlight a great need for additional studies, especially those examining cellular and organ responses in bumble bees exposed to neonicotinoids. Environ Toxicol Chem 2021;40:309–322. © 2020 SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA.